Efeito do TKI-258 sobre a proliferação celular em carcinoma epidermoide oral in vitro - SILVEIRA, Isadora Caixeta da (2018)
Oral squamous cell carcinoma presents high mortality rates. Tyrosine kinase receptors, FGFRs, PDGFRs and, VEGFRs, are amplified and/or overexpressed in this neoplasm and are blocked by the inhibitor TKI-258. These receptors activate PI3K, an intracellular protein that is often associated with carcinogenesis, that can be blocked by inhibitors LY294002 and Wortmannin. The aim of this study was to evaluate the effect of TKI-258 treatment on cell proliferation, and the role of PI3K protein in signaling pathways inhibited by this inhibitor in oral squamous cell carcinoma in vitro. Through the BrdU incorporation assays and KI-67 immunoexpression, cell proliferation markers, SCC-4 cells of oral squamous cell carcinoma were quantified and treated for 6 h with TKI-258 (1, 5 and 10 μM); LY294002 60 μM (LY) and/or Wortmannin 2 μM (WTN); TKI-258 5 μM only or associated with LY or WTN; and, 5 μM TKI-258 combined with LY and WTN. A significance of p<0.05 was considered. Treatment with TKI-258 reduced the proliferation rate in SCC-4 cells incorporated BrdU [F(3,11) =120.807, p<0.0001] and immunoexpressed KI-67 [F(3,11) = 222.379, p<0.0001]. The reduction percentage was also lower after treatment with PI3K, LY and/or WTN inhibitors, incorporation of BrdU [F(3,11) = 477.578, p<0.0001] and KI-67 [F(3,11) = 421.762, p<0.0001]. And, the association of 5 μM TKI-258 with LY and/or WTN further decreased the proliferation rate in BrdU incorporation [F(3.11) = 252.324, p<0.0001] and KI-67 immunoexpression [F(3,11) = 295.346, p<0.0001]. The results obtained in this study demonstrated that TKI-258 exhibits an antiproliferative effect on SCC-4 cells of OSCC and this process may possibly be regulated by the tyrosine kinase receptors blocked by that inhibitor, by means of PI3K dependent and independent pathways.